Estimation of the Iron Loss in Deep-Sea Permanent Magnet Motors considering Seawater Compressive Stress. (6th August 2014) - Xu, Yongxiang; Wei, Yanyu; Zou, Jibin; Li, Jianjun; Qi, Wenjuan; Li, Yong
Abstract : Deep-sea permanent magnet motor equipped with fluid compensated pressure-tolerant system is compressed by the high pressure fluid both outside and inside. The induced stress distribution in stator core is significantly different from that in land type motor. Its effect on the magnetic properties of stator core is important for deep-sea motor designers but seldom reported. In this paper, the stress distribution in stator core, regarding the seawater compressive stress, is calculated by 2D finite element method (FEM). The effect of compressive stress on magnetic properties of electrical steel sheet, that is, permeability, BH curves, and BW curves, is also measured. Then, based on the measured magnetic properties and calculated stress distribution, the stator iron loss is estimated by stress-electromagnetics-coupling FEM. At last the estimation is verified by experiment. Both the calculated and measured results show that stator iron loss increases obviously with the seawater compressive stress.